2009
DOI: 10.1016/j.memsci.2008.12.016
|View full text |Cite
|
Sign up to set email alerts
|

The role of NOM fouling for the retention of estradiol and ibuprofen during ultrafiltration

Abstract: The impact of membrane fouling by natural organic matter (NOM) on the behavior of micropollutants during ultrafiltration (UF) was investigated. Batch experiments with radioactively labeled estradiol and ibuprofen in the presence of NOM model compounds (alginate, Nordic aquatic and Aldrich humic acid) were performed using a hydrophilic and a hydrophobic membrane. The results indicate that the impact of the NOM fractions studied on micropollutant retention correlated with the fouling mechanism of the individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 44 publications
5
44
1
2
Order By: Relevance
“…Estudos recentes demonstram que o fenômeno de fouling associado à presença de ácidos húmicos e polissacarídeos aumenta significativamente a retenção de estradiol em processos de ultrafiltração. 10 Este tipo de efeito é particularmente importante na filtração de amostras mais complexas, como águas naturais e esgoto. Neste caso, fenômenos de clogging e fouling são bastante comuns, 11 o que limita o volume de amostra, aumenta o tempo de filtração e diminui a capacidade de recuperação de certos micropoluentes.…”
Section: Resultsunclassified
“…Estudos recentes demonstram que o fenômeno de fouling associado à presença de ácidos húmicos e polissacarídeos aumenta significativamente a retenção de estradiol em processos de ultrafiltração. 10 Este tipo de efeito é particularmente importante na filtração de amostras mais complexas, como águas naturais e esgoto. Neste caso, fenômenos de clogging e fouling são bastante comuns, 11 o que limita o volume de amostra, aumenta o tempo de filtração e diminui a capacidade de recuperação de certos micropoluentes.…”
Section: Resultsunclassified
“…However, micropollutants can be removed via interaction with natural organic matter (NOM) or adsorption onto membrane polymers. Jermann et al (2009) investigated the removal efficiencies of ibuprofen and estradiol by UF without existing the NOM. In hydrophilic UF membrane, elimination rate of ibuprofen and estradiol were found negligible and 8 % respectively.…”
Section: Membrane Processesmentioning
confidence: 99%
“…Membrane material can also have a significant influence on adsorption [11]. For example, Jermann et al [12] observed up to 80% adsorption of estradiol to polyethersulfone ultrafiltration (UF) membranes compared to only 8% adsorption to regenerated cellulose UF membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Within the literature, reports on the influence of solute-foulant interactions appear to be highly variable and dependent on properties of the micropollutant, such as charge and molecular weight, as well as organic matter properties and membrane material. Several studies have attributed improved steroidal hormone removal in the presence of organic matter to solute-foulant interactions [10,12]. Three main mechanisms can influence micropollutant removal in fouled membranes including concentration polarisation, pore blocking and adsorption to the fouling layer [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation